Reit market price and nav deviations: evidence from Malaysia - Yip, Kang Li (2019)
Malaysian REIT market has experienced huge improvement since year 2005. This study aimed to investigate the determinants that caused deviation of M-REIT market price from its NAV. A total of 18 M-REIT companies are included in the investigation, which the respective REIT companies are observed for a period of 13 years, from year 2005 to year 2017. The statistical data illustrated that most M-REITs are traded below its NAV. This research adopted fixed effects model in examining the determinants of M-REIT market valuation. In terms of firm specific characteristics, the gearing ratio, firm size, profitability, dividend yield and proportion of long-term debt appeared to be insignificant in affecting the deviation of M-REIT price from its NAV. Unfortunately, the trading volume, major unitholding, occupancy rate, proportion of fixed loan and liquidity bid-ask spread are reported to be highly significant in influencing M-REIT price to NAV. Indeed, investment properties diversification and gender diversity are insignificant in affecting M-REIT market price valuation. The empirical results of this study suggested that M-REIT companies should further improve their properties occupancy rate to attain higher market price. It is suggested that Malaysian authority should increase the mandatory unitholding spread of total listed units to promote the trading liquidity of M-REIT market.